Climate Change: Impacts, Adaptation, and Mitigation - Rice, Charles W. (Kansas State University, 2012)
Agriculture offers many opportunities for greenhouse gas mitigation through reduced tillage, cover crops, fertility management, and water management. No-tillage cropping systems improve soil fertility and conserve soil moisture while also reducing energetic inputs and sequestering carbon. Biofuels also offer mitigation opportunities. Life cycle assessments of corn stover, P. sorghum, switchgrass, and miscanthus indicate substantially lower greenhouse gas emissions than conventional gasoline. A number of other projects on campus are related to climate change and agriculture including collaborative work with other U.S. and international institutions.
Keywords: Climate change; Mitigation; Biofuels; No-till; Nitrogen management